Strategi Perencanaan Jaringan Transportasi Menggunakan Model Matematika Teknik Sipil - Jun Fajar Krisman Giawa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Transportation network planning is an important aspect in civil engineering that is related to infrastructure development to support community mobility. One way to handle this planning is to use mathematical models. Mathematical models function to model various aspects of the transportation system, from traffic flow, distribution, to efficient infrastructure planning. In this context, models can be applied to minimize costs, travel times, or improve traffic distribution between points in a transportation network. Basically, mathematical models for transportation network planning consist of several types, such as optimization models, flow models, and simulation models. Optimization models are often used to determine the best route or optimal network capacity. Meanwhile, flow models are used to analyze how traffic moves in the network and how system adjustments can reduce congestion. On the other hand, simulation models allow designers to test various scenarios dynamically, providing a more realistic picture of potential problems that may arise in the field. In addition, the use of mathematical models in planning transportation networks also takes into account external factors such as population growth, changes in travel patterns, and economic development. Therefore, a mathematical approach in transport network planning is not only useful for designing efficient infrastructure, but also for planning sustainable traffic management in the long term.